Characterization of hard Ti-W-N films deposited by reactive d.c. magnetron sputtering - Shaginyan, Leonid R. (Kovine zlitine tehnologije, 1999)
Ti-W-N films were deposited by reactive d.c. magnetron sputtering from a W-Ti (30 at.%) target in a mixture of argon and nitrogen onto steel and silicon substrates. The substrates were placed at a distance of 50mm from the target. The total pressure prior to the ignition of the discharge was kept at 0.5 Pa, while the total gas flow was set to 50 sccm. The typical deposition parameters were: substrate temperature 320°C, deposition rate 3 nm/s, film thickness 3.5 ?$μ$?m, substrate bias -100 V, and mean substrate ion current density 1.2 mA/?$cm^2$?. The crystal structure, composition and micro-hardness were studied as a function of deposition parameters, i.e., nitrogen content in the working gas mixture, substrate ion current density and substrate bias. The films containing less than 30 at.% nitrogen were composed of bcc W and, possibly hcp Ti phases. The hardness of these films increased with increasing nitrogen content from 25 GPa for o at.% N up to a maximum of approximately 60 GPa for 25 at.% N. This was accompanied by increasing micraostrain, as revealed by an analysis of the broadening of the X-ray reflections. The films with a nitrogen content over 30 at.% were characterized by a micro-hardnessof about 40 GPa and by X-ray reflections indicative of an fcc phase.
Keywords: kovinske prevleke; titan; volfram; nitridi; naprševanje; mikrostruktura; trdota